Determinants Of The Profitability Of Islamic Commercial Banks In Indonesia - Tusiyani, Ira; Yudiana, Fetria Eka (WADIAH, 2024)
Factors that influence bank profitability can come from various performances. One of the profitability ratios used is Return On Assets (ROA), which is a profitability ratio that shows the percentage of profits to determine the company's efficiency in managing assets to generate profits. Other factors that influence profitability include Third Party Funds and Non-Performing Finance. The aim of this research is to examine the influence of DPK and NPF on profit sharing financing at Islamic commercial banks in Indonesia in 2016-2020. This type of research is quantitative, using data collection techniques with purpose sampling. This research also uses panel data analysis techniques, namely a combination of time series and cross section data. The panel data regression model is a combination of data from a number of objects within a certain time period. The total population is 14 Islamic commercial banks in Indonesia, with a sample size of 10 Islamic commercial banks in accordance with the characteristics of this research. This research uses a panel data regression analysis method which is processed using eviews 10. The results of this research are that DPK has a negative and insignificant effect on profitability. NPF has a positive and insignificant effect on profitability. Profit sharing financing has a positive and significant effect on profitability. DPK has a positive and significant effect on profit sharing financing. NPF has a negative and significant effect on profit sharing financing. Profit sharing financing does not mediate TPF and NPF on profitability.